ВЛИЯНИЕ НАРУШЕНИЯ ЦИРКУЛЯЦИИ ДИСТИЛЛЯТА НА ТЕРМОМЕХАНИЧЕСКИЕ НАПРЯЖЕНИЯ В ИЗОЛЯЦИИ ОБМОТКИ СТАТОРА ТУРБОГЕНЕРАТОРА МОЩНОСТЬЮ 800 МВт - Кучинский, К.А. (Інститут електродинаміки НАН України, Київ, 2013)
The technique of computer calculation of thermomechanical stress in isolation of the turbogenerator stator winding with a full water cooling is developed. In a technique basis the numerical method of final elements realised in a package of applied programs is assumed. The comparative analysis of results of computational researches of a thermomechanical condition of isolation of the stator winding rod of the turbogenerator by power 800 MW in a nominal condition taking into account change of a temperature condition of its elements at water consumption decrease is carried out. It is founded, at what water consumption and on what sections of the rod of magnitude of thermomechanical stress attain the dangerous values exceeding an ultimate strength of the material. References 8, figures 3.